Profil Klirens Kreatinin pada Pasien Penyakit Ginjal di RSUD Dr. Doris Sylvanus Kota Palangka Raya: Profile of Creatinine Clearance in Kidney Disease Patients in Dr. Doris Sylvanus Hospital Palangka Raya City - Nova Nova; Fera Sartika; Suratno Suratno (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Kidney disease is the loss of kidney function. This results in salt retention, nitrogen wastewater, and a decrease in urine volume. Kidney disorders are characterized by structural or functional abnormalities of the kidneys that last more than three months. Indicators to see the ability of renal glomerular filtration can be done by checking creatinine clearance. Creatinine clearance is the number of millimeters of plasma cleared of creatinine by the kidneys in one minute. This study aimed to determine the level of creatinine clearance in patients with kidney disease in RSUD dr. Doris Sylvanus City of Palangka Raya. This research was conducted by quantitative descriptive method, with the number of research samples as many as 15 outpatient kidney disease patients who had not performed hemodialysis at the Clinical Pathology Laboratory of RSUD dr. Doris Sylvanus Palangka Raya, with a sampling technique in the form of Accidental Sampling. The examination method used is the measurement of creatinine clearance as a marker of the glomerular filtration rate (GFR) using the Cockroft-Gault formula. The results showed that based on the value of normal creatinine clearance, as much as 7%, and the decreased value of creatinine clearance, as much as 93%.